Luminescence and photoconductivity of poly-n-epoxypropylcarbazole with intramolecular charge transfer compounds - Davidenko, N.A.; Kuvshinsky, N.G.; Syromiatnikov, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Features of charges photogeneration in the films of poly-N-epoxypropylcarbazole doped with compounds with intramolecular charge transfer used in holographic recording media are investigated. Influence of an external electric field on the quantum yield of charges photogeneration and photoluminescence as studied. Different dependencies on the temperature of such two parameters within the wide temperature range were shown. The assumption of the tunnel mechanism of electron-hole pair formation from an excited molecule of compound with intramolecular charge transfer was made.